The Effect of Cooling Media on Tensile Strength of Medium Carbon Steel in Post Welding Process Using Electric Welding (SMAW) with E7018 Electrodes - Zulhafril, Herman; Jasman, Jasman; Tespoer, Kimberly June (Universitas Negeri Padang, 2020)
The use of cooling media in post welding process will affect the tensile strength of a material. This study aims to determine how much the influence of using cooling media in post welding and which cooling media is appropriate to use. The process is done by comparing the tensile strength of each cooling media, namely the cooling media of water, air, and coolant. The use of cooling media is carried out after the welding process, until the material that is ready to be welded reaches room temperature. Based on the experiments that have been conducted, the use of post-welding cooling media affects the tensile strength of medium carbon steel with the highest effect on the water cooling media, then the coolant media, and the lowest is the air cooling media. Therefore, the choice of the use of cooling media significantly affects the tensile strength of medium carbon steel in the post-welding process.